Step
*
1
of Lemma
eo-strict-forward-pred
1. Info : Type
2. eo : EO+(Info)
3. e : E
4. e' : E
5. ¬↑first(e')
6. (loc(pred(e')) = loc(e') ∈ Id)
∧ (pred(e') < e')
∧ (∀e'@0:E. (e'@0 < e') 
⇒ ((e'@0 = pred(e') ∈ E) ∨ (e'@0 < pred(e'))) supposing loc(e'@0) = loc(e') ∈ Id)
7. ¬↑first(e')
8. (loc(pred(e')) = loc(e') ∈ Id)
∧ (pred(e') < e')
∧ (∀e'@0:E. (e'@0 < e') 
⇒ ((e'@0 = pred(e') ∈ E) ∨ (e'@0 < pred(e'))) supposing loc(e'@0) = loc(e') ∈ Id)
⊢ pred(e') = pred(e') ∈ E
BY
{ (SplitAndHyps THEN InstHyp [⌈pred(e')⌉] 8⋅) }
1
.....wf..... 
1. Info : Type
2. eo : EO+(Info)
3. e : E
4. e' : E
5. ¬↑first(e')
6. loc(pred(e')) = loc(e') ∈ Id
7. (pred(e') < e')
8. ∀e'@0:E. (e'@0 < e') 
⇒ ((e'@0 = pred(e') ∈ E) ∨ (e'@0 < pred(e'))) supposing loc(e'@0) = loc(e') ∈ Id
9. ¬↑first(e')
10. loc(pred(e')) = loc(e') ∈ Id
11. (pred(e') < e')
12. ∀e'@0:E. (e'@0 < e') 
⇒ ((e'@0 = pred(e') ∈ E) ∨ (e'@0 < pred(e'))) supposing loc(e'@0) = loc(e') ∈ Id
⊢ pred(e') ∈ E
2
.....antecedent..... 
1. Info : Type
2. eo : EO+(Info)
3. e : E
4. e' : E
5. ¬↑first(e')
6. loc(pred(e')) = loc(e') ∈ Id
7. (pred(e') < e')
8. ∀e'@0:E. (e'@0 < e') 
⇒ ((e'@0 = pred(e') ∈ E) ∨ (e'@0 < pred(e'))) supposing loc(e'@0) = loc(e') ∈ Id
9. ¬↑first(e')
10. loc(pred(e')) = loc(e') ∈ Id
11. (pred(e') < e')
12. ∀e'@0:E. (e'@0 < e') 
⇒ ((e'@0 = pred(e') ∈ E) ∨ (e'@0 < pred(e'))) supposing loc(e'@0) = loc(e') ∈ Id
⊢ loc(pred(e')) = loc(e') ∈ Id
3
.....antecedent..... 
1. Info : Type
2. eo : EO+(Info)
3. e : E
4. e' : E
5. ¬↑first(e')
6. loc(pred(e')) = loc(e') ∈ Id
7. (pred(e') < e')
8. ∀e'@0:E. (e'@0 < e') 
⇒ ((e'@0 = pred(e') ∈ E) ∨ (e'@0 < pred(e'))) supposing loc(e'@0) = loc(e') ∈ Id
9. ¬↑first(e')
10. loc(pred(e')) = loc(e') ∈ Id
11. (pred(e') < e')
12. ∀e'@0:E. (e'@0 < e') 
⇒ ((e'@0 = pred(e') ∈ E) ∨ (e'@0 < pred(e'))) supposing loc(e'@0) = loc(e') ∈ Id
⊢ (pred(e') < e')
4
1. Info : Type
2. eo : EO+(Info)
3. e : E
4. e' : E
5. ¬↑first(e')
6. loc(pred(e')) = loc(e') ∈ Id
7. (pred(e') < e')
8. ∀e'@0:E. (e'@0 < e') 
⇒ ((e'@0 = pred(e') ∈ E) ∨ (e'@0 < pred(e'))) supposing loc(e'@0) = loc(e') ∈ Id
9. ¬↑first(e')
10. loc(pred(e')) = loc(e') ∈ Id
11. (pred(e') < e')
12. ∀e'@0:E. (e'@0 < e') 
⇒ ((e'@0 = pred(e') ∈ E) ∨ (e'@0 < pred(e'))) supposing loc(e'@0) = loc(e') ∈ Id
13. (pred(e') = pred(e') ∈ E) ∨ (pred(e') < pred(e'))
⊢ pred(e') = pred(e') ∈ E
Latex:
1.  Info  :  Type
2.  eo  :  EO+(Info)
3.  e  :  E
4.  e'  :  E
5.  \mneg{}\muparrow{}first(e')
6.  (loc(pred(e'))  =  loc(e'))
\mwedge{}  (pred(e')  <  e')
\mwedge{}  (\mforall{}e'@0:E.  (e'@0  <  e')  {}\mRightarrow{}  ((e'@0  =  pred(e'))  \mvee{}  (e'@0  <  pred(e')))  supposing  loc(e'@0)  =  loc(e'))
7.  \mneg{}\muparrow{}first(e')
8.  (loc(pred(e'))  =  loc(e'))
\mwedge{}  (pred(e')  <  e')
\mwedge{}  (\mforall{}e'@0:E.  (e'@0  <  e')  {}\mRightarrow{}  ((e'@0  =  pred(e'))  \mvee{}  (e'@0  <  pred(e')))  supposing  loc(e'@0)  =  loc(e'))
\mvdash{}  pred(e')  =  pred(e')
By
(SplitAndHyps  THEN  InstHyp  [\mkleeneopen{}pred(e')\mkleeneclose{}]  8\mcdot{})
Home
Index